Association of metallothionein 2A rs10636 with low mean corpuscular volume (MCV), low mean corpuscular haemoglobin (MCH) in healthy Taiwanese - Rong-Fu Chen; Po-Ming Chen; Chau-Shiung Pan; Chieh-Cheng Huang; En-Pei Isabel Chiang (Scientific Reports, 2023)
Abstract Human metallothionein-2A (MT2A) protein participates in metal homeostasis, detoxification, oxidative stress reduction, and immune defense. It decreases heavy metal ions and reactive oxygen species (ROS) during injury of cells and tissues. The single nucleotide polymorphisms at the MT2A gene have been associated in various human diseases including cancer. The current study aimed to elucidate associations between MT2A genotypes with the clinical, biochemical, and molecular characteristics that potentially related to lowered MT2A ex-pression. One hundred and forty-one healthy Taiwanese subjects were enrolled from Changhua Show-Chwan Memorial Hospital. Clinical, biochemical and molecular characteristics including the frequent minor allele SNPs, rs28366003 and rs10636, within the MT2A gene were determined. The genotype distribution of MT2A rs10636 fits the Hardy–Weinberg equilibrium. The significant associations with gradually decline of mean corpuscular volume (MCV) and mean corpuscular hemoglobin (MCH) were identified with MT2A rs10636 and rs28366003 using analysis of variance (ANOVA) with Tukey’s analysis as a post hoc test. We further validated the correlations between the expressions of genes in erythropoiesis, cholesterol synthesis, platelet synthesis, insulin with MT2A using the web-based Gene Expression Profiling Interactive Analysis (GEPIA) databases. The results revealed that hypoxia-inducible factor 1α (HIF-1α), erythropoietin (EPO), lipoprotein lipase (LPL), and lecithin-cholesterol acyltransferase (LCAT) mRNA ex-pression are significantly correlated with MT2A mRNA expression. In conclusion, these results suggested that genetic variations of MT2A rs10636 and rs28366003 might be an important risk factor for erythropoiesis in the Taiwanese general population.